Analysis of the maximum precipitation data in northwestern São Paulo by theory of extreme values (Research, Society and Development, 2020)
Predicting the behavior of extreme phenomena becomes extremely important for the entire population, due to the consequences caused by global warming, which makes the study of Extreme Value Theory (TVE) increasingly essential in studies of environmental variables. Applied for the purpose of describing the behavior of rare events, it has been applied in meteorology to maximum rainfall, minimum temperatures, maximum winds, since such information is of great importance for urban, industrial, agronomic planning and mitigation public policies of impulse and development of cities and society. Considering the importance of knowing the possible maximum monthly rainfall, this study aims to estimate the probability of maximum expected monthly rainfall for different periods using a historical series of rainfall data from Ilha Solteira region, as well as to verify the level of rainfall. of data adjustment to the Generalized Extreme Values (GEV) model using the maximum likelihood method for estimating the model parameters and verification of the adjustment in all considered rainfall periods, respectively. Gumbel distribution was the most appropriate for this case study, except in the dry season of the region.